2012
DOI: 10.1017/s2045796011000801
|View full text |Cite
|
Sign up to set email alerts
|

The narrative epidemiology of L'Aquila 2009 earthquake

Abstract: The authors describe their experience working and living in L'Aquila, where at 3.32 a.m., early in the morning of 6 April 2009, a 6.3 Richter magnitude earthquake caused serious damages to this 13th century town (with a population of 72 000 and a health district of 103 788), in the mountainous Abruzzo region and to several medieval hill villages in the surrounding areas: 309 residents were killed, over 1600 were injured, 66 000 residents were displaced, and, the centre of L'Aquila, the main historical and arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Published research concerned with resilience and health commonly focus on responses to communal threats (Eggerman and Panter-Brick 2010, Hobfoll, Mancini et al 2011, Vaughan, Tinker et al 2012) and natural disasters (Rajkumar, Premkumar et al 2008, Springgate, Wennerstrom et al 2011, Casacchia, Pollice et al 2012, Xu and He 2012. Researchers also consider responses to personal trauma, including sudden or violent loss (Kristensen, Weisaeth et al 2012), being a victim of violence (Zraly and Nyirazinyoye 2010), physical injury (Quayle and Schanke 2010), stroke (Ostir, Berges et al 2008), material adversity (Canvin, Marttila et al 2009) or an actual or potential diagnosis of cancer (Ho, Ho et al 2010, Hou, Law et al 2010).…”
Section: Resilience and Depressionmentioning
confidence: 99%
“…Published research concerned with resilience and health commonly focus on responses to communal threats (Eggerman and Panter-Brick 2010, Hobfoll, Mancini et al 2011, Vaughan, Tinker et al 2012) and natural disasters (Rajkumar, Premkumar et al 2008, Springgate, Wennerstrom et al 2011, Casacchia, Pollice et al 2012, Xu and He 2012. Researchers also consider responses to personal trauma, including sudden or violent loss (Kristensen, Weisaeth et al 2012), being a victim of violence (Zraly and Nyirazinyoye 2010), physical injury (Quayle and Schanke 2010), stroke (Ostir, Berges et al 2008), material adversity (Canvin, Marttila et al 2009) or an actual or potential diagnosis of cancer (Ho, Ho et al 2010, Hou, Law et al 2010).…”
Section: Resilience and Depressionmentioning
confidence: 99%
“…Other people stayed with friends and relatives throughout Italy. Moreover, villages around the L’Aquila area were severely damaged [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Casacchia et al (2012) reported that the 6-month prevalence rate of PTSD among L’Aquila survivors ranged from 12% to 37.5% in different population samples (clinical and not-clinical sample [1]. …”
Section: Introductionmentioning
confidence: 99%
“…The fourth limitation could be ascribed to the use of a self-report instrument, that is the SASRQ, as a diagnostic tool for ASD, but the poor emergency conditions in which local mental health professionals were working immediately after the earthquake did not allow for the administration of clinical interviews. As medical doctors, they were both victims and observers of the disaster [64]. …”
Section: Discussionmentioning
confidence: 99%
“…The earthquake caused serious damage to the 13th-century town of L’Aquila in the mountainous Abruzzo region and to several medieval hill villages in the surrounding areas, killing 309 residents, injuring over 1,600 residents, and leaving approximately 70,000 people homeless [64]. Approximately 44,000 people found accommodation in tented camps close to their place of residence, and a further 20,000 were housed in hotels on the Abruzzo Adriatic Sea coast.…”
Section: Introductionmentioning
confidence: 99%